Karakterisasi lingkungan perairan Teluk Talengen Kabupaten Kepulauan Sangihe sebagai kawasan budidaya rumput laut Kappaphycus alvarezii - Schaduw, Joshian N.W.; Ngangi, Edwin (Universitas Sam Ratulangi, 2015)
This paper was the result of a feasibility analysis of Talengen Bay Waters for aquaculture of Kappaphycus alvarezii. Feasibility analysis of water was based on the environmental data and water quality parameters of Talengen Bay. One mistake in the development of aquaculture is environmentally unsuitable. In order to develop aquaculture properly, appropriate water conditions data were required. Suitable aquatic environments are required by organisms for their survival because they are related to the patterns and behavior of the biota. In connection with the problems of mariculture at Talengen Bay, several efforts were required to overcome them. One of the efforts was made through this study that was assessment of appropriate location for the cultivation of seaweed. Talengen Gulf was located in Â in the territory of KampungÂ Talengen andÂ Kampung Bunga Lawang, Central District of Tabukan, Sangihe Islands Regency, North Sulawesi. Laboratory analysis was conducted at the Laboratory of Industrial Baristand Manado. Determination of research stations done intentionally (purposive sampling). Based on the results obtained it could then be concluded that the condition of the aquatic environment and water quality parameters in the Talengen Bay were categorized as suitable for seaweed cultivation K. alvarezii. Phosphate, nitrate, Total Suspended Solid data were needed to be considered. Keywords: Environmental characteristics, seaweed, aquaculture; Kappaphycus alvarezii